PERAN GURU PPKn DALAM MENANAMKAN NILAI-NILAI KARAKTER MELALUI KANTIN KEJUJURAN DI MTs MUHAMMADIYAH 01 TEGALOMBO KABUPATEN PACITAN - Beti Andriani; Sutrisno Sutrisno; Sunarto Sunarto (EDUPEDIA, 2017)
This study aims to 1) describe the implementation of "an effective self-service cafetaria to build characters value? 2) describe civic education teachers role in building students' character values through "an effective self-service cafetaria". This study is categorized as a qualitatve study in Mts Muhammadiyah 01 Tegalombo, Ponorogo regency. It is conducted by utilizing observation, interview, and documentation as the data collection techniques. The informants of this study are the headmaster, civic education teachers, the staffs of "a self-service cafetaria" and VII, VIII, and IX grade students. This study gains some results. 1) an effective self-service cafeteria can build characters values by optimizing school-management' rules and performance of the headmaster, school faculties and school curriculum development, practicing character values in the "a self-service cafetaria" implementation, and having a good operational standard for self-service cafeteria including tidiness, discipline, health, and hygiene, and applying a consistent rule and punishment for creating a good participation from the students.2) The role of civic education teachers in building students' character values through "a self-service cafeteria" is surely important. It also relates to civic education learning which is taught in the classrooms by those teachers and this lesson educates the students to comprehend the material. Therefore, the students can put the theories into practical, through a self-service cafeteria. It can be concuded that a self-service cafeteria management so influences students' participation. It is because a good management and discipline self-service cafeteria will create a clean and tidy environment. Therefore, the students will be more comfortable and motivated to buy in this self-service cafeteria. In addition, they can build their good character values.